The not so over-the-counter status of emergency contraception in Ontario: A mixed methods study with pharmacists - Andréanne Chaumont; Angel M. Foster (Canadian Science Publishing, 2017)
Introduction: In Canada, the progestin-only dedicated pill is the most widely used method of emergency contraception (EC). This method gained over-the-counter status in Ontario in 2008. Our mixed methods study explored the progestin-only EC knowledge, attitudes, and provision practices of Ontario pharmacists. Methods: From June 2015 to October 2015, we collected 198 mailed surveys from Ontarian pharmacy representatives and conducted 17 in-depth interviews with a subset of respondents. We analyzed these data using descriptive statistics and for content and themes. Results: Results from our English/French bilingual survey indicate that respondents' knowledge is generally accurate, but confusion persists about the mechanism of action and the number of times the drug can be used in one menstrual cycle. Nearly half (49%) of our survey respondents indicated that progestin-only EC pills are only available behind the counter. Interviewees strongly supported the introduction and promotion of more effective methods of EC in Ontario. Conclusion: Continuing education focusing on both the regulatory status of progestin-only EC and information about the medication appears warranted. Health Canada's recent approval of ulipristal acetate for use as a post-coital contraceptive may provide a window of opportunity for engaging with health service providers, including pharmacists, about all available modalities of EC in Canada.